ANALISIS PERGESERAN FUNGSI LAHAN DI KECAMATAN KOTA UTARA KOTA GORONTALO. - Tatura, Lydia Surijani (Sainstek, 2009)
Since the Gorontalo Province was established as stated on the national law number 38 year 2000, the Gorontalo city become a part of the province area and became the capital of the new province. As the capital Gorontalo city, it has a strategic role that makes possible providing opportunity in developing economy, industry and trade, transportation services and other development sector. The growth and the development give positive impact to the development, but negative impact to the people and the natural resources. In the other side, that cause emerging of new environmental problems. The function of productive land as one of the people life resources mostly convert to other function as governmental building, trade building, people residence and other infrastructure. This research was conducted in Gorontalo city on the productive area in the 10 sub-subdistrict of the Kota Utara subdistrict. The physical area mapping used the Gorontalo city land unit map 1999 was compared to utility of the land after 10 years (2009). This research conducted by using descriptive methode. Primary data analisys uses descriptive methode with its results as tables, pictures, photos. The result of this research shows the productive land conversion in Kota Utara subdistrict + 102,178 Ha from field to kinds of industry utility, trading, residences, and public facilities. The reason of land function convertion, based on people perception, is city region government. In for utilizing the productive land, wich is based on the most important economic criteria, welfare, the increasing the city original income and investation . The environmental criteria with local priority, the most contaminated is residence sector, and for the natural resources and land availability are agricultural subsector. The conclusion of this research, that productive land function conversion in Kota Utara subdistrict arrange development area which is not suitable with the aim and the plan that stated on RTRW Gorontalo City 2001-2011. KEY WORD : Land Function, Convertion.